2016
DOI: 10.3389/fpsyg.2016.00522
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Semantic Emotion Space Using a 3D Hypercube-Projection: An Innovative Analytical Approach for the Psychology of Emotions

Abstract: The widely accepted two-dimensional circumplex model of emotions posits that most instances of human emotional experience can be understood within the two general dimensions of valence and activation. Currently, this model is facing some criticism, because complex emotions in particular are hard to define within only these two general dimensions. The present theory-driven study introduces an innovative analytical approach working in a way other than the conventional, two-dimensional paradigm. The main goal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…The flexibility of valence in awe is somewhat unusual for an emotion, though there are other examples that follow this pattern, such as nostalgia (Wildschut et al, 2006). Since conventional models of emotions typically do not admit this degree of complexity (Trnka et al, 2016), Keltner and Haidt (2003) suggested the existence of different emotional themes (i.e., threat, beauty, virtue, power, and uncanny) that “flavor” awe (Keltner and Haidt, 2003; p. 304), creating a kind of family of awe-related states. For example, awe arising from threatening stimuli can be a source of negative valence, as they write, “danger causes an experience of awe to be flavored by feelings of fear” (Keltner and Haidt, 2003; p. 304).…”
Section: Research On Awementioning
confidence: 99%
“…The flexibility of valence in awe is somewhat unusual for an emotion, though there are other examples that follow this pattern, such as nostalgia (Wildschut et al, 2006). Since conventional models of emotions typically do not admit this degree of complexity (Trnka et al, 2016), Keltner and Haidt (2003) suggested the existence of different emotional themes (i.e., threat, beauty, virtue, power, and uncanny) that “flavor” awe (Keltner and Haidt, 2003; p. 304), creating a kind of family of awe-related states. For example, awe arising from threatening stimuli can be a source of negative valence, as they write, “danger causes an experience of awe to be flavored by feelings of fear” (Keltner and Haidt, 2003; p. 304).…”
Section: Research On Awementioning
confidence: 99%
“…According to this model, an emotion can be defined by its position in a three-dimensional space that characterizes states as positive or negative (Evaluation), dominant or submissive (Potency), and active or passive (Activity). Later versions of the EPA model have often referred to the three dimensions as Valence or Pleasure (for Evaluation), Arousal or Intensity (for Activity), and Dominance or Controllability (for Potency) (e.g., Mehrabian & Russell, 1974;Trnka, La cev, Balcar, Ku ska, & Tavel, 2016). While we consider these terms as largely interchangeable, it is important to point out some nuances that set them apart.…”
Section: Introductionmentioning
confidence: 99%
“…All languages include words that relate to emotional experiences and moods. Such linguistic labels for emotion categories in language are called emotion terms, emotion words or emotion names (Hupka, Lenton, & Hutchinson, 1999;Trnka, Lacev, Balcar, Kuška, & Tavel, 2016). Emotion terms help people to understand their own emotions, and they are conventionally understood as abstract representations with which people compare their real, everyday emotional experiences (but see, e.g., Bickhard, 2007;or Cowley, Stephen, & Harvey, 2016 for different operational defining of language).…”
Section: Emotion Languagementioning
confidence: 99%